2022
DOI: 10.1039/d2bm00337f
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced antitumor activity of the polymeric conjugate covalently coupled with docetaxel and docosahexaenoic acid

Abstract: Docetaxel (DTX) has been widely used for treatment of many types of cancer. However, DTX is poor water soluble and commercial DTX is formulated in nonionic surfactant polysorbate 80 and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…At the end of the experiment, 6 mg/kg parent DTX treatment inhibited tumor growth by 16.2%, while the conjugate 18 treatment at the dose of 6 and 12 mg/kg inhibited tumor growth by 32.6% and 59.0%, respectively ( Figure 6(A,C) ). The tumor growth inhibitory efficacy of the conjugate 18 was similar to that of tandem type of dual-drug conjugate we reported previously (Dong et al., 2022 ). Our previous study showed that the treatment of 6 mg/kg of parent DTX, 6 mg/kg and 12 mg/kg of tandem type of dual-drug conjugate decreased the tumor volume by 19.6%, 36.8%, and 58.8% in H460 xenograft under the same schedule of administration as this study, respectively.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…At the end of the experiment, 6 mg/kg parent DTX treatment inhibited tumor growth by 16.2%, while the conjugate 18 treatment at the dose of 6 and 12 mg/kg inhibited tumor growth by 32.6% and 59.0%, respectively ( Figure 6(A,C) ). The tumor growth inhibitory efficacy of the conjugate 18 was similar to that of tandem type of dual-drug conjugate we reported previously (Dong et al., 2022 ). Our previous study showed that the treatment of 6 mg/kg of parent DTX, 6 mg/kg and 12 mg/kg of tandem type of dual-drug conjugate decreased the tumor volume by 19.6%, 36.8%, and 58.8% in H460 xenograft under the same schedule of administration as this study, respectively.…”
Section: Resultssupporting
confidence: 84%
“…Surprisingly, 12 mg/kg of conjugate 18 eradicated all the tumors on day 18 ( Figure 6(F) ). The antitumor effect of the conjugate 18 exceeded that of tandem type of dual-drug conjugate we reported previously, in which the treatment of tandem type of dual-drug conjugate with the dose of 12 mg/kg eliminated 4 out 6 xenograft tumors in MCF-7 bearing nude mice after four times of administration once a week (Dong et al., 2022 ). The single-drug conjugate dextran-DTX at the dose of 12 mg/kg eradicated 2 tumors on day 18 and 5 tumors on day 21 ( Figure 6(F) ).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Additionally, it can hinder tumor invasion and metastasis by reducing tumor cell rolling, adhesion, and migration. Importantly, previous research has shown that DHA can increase the susceptibility of cancer cells to chemotherapeutic agents without amplifying the toxicity to healthy tissues [ 209 , 210 ]. Both of these factors have prompted researchers to incorporate marine-derived PUFAs into drug delivery systems as assemblers or drug loaders for the purpose of synthetically enhancing cancer treatment.…”
Section: Marine Food Sources-derived Fatty Acid-based Nanomaterialsmentioning
confidence: 99%
“…One of the explored strategies is that of combining the treatment with DTX with that of other antineoplastic agents [21,22]. One possible combination strategy that has been largely explored in breast cancer and has been shown to induce a considerable increase in the DTX antineoplastic efficacy is the combined treatment of DTX with omega-3 polyunsaturated fatty acids (PUFAs) and, in particular, with the long-chain omega-3 PUFA docosahexaenoic acid (DHA, 22:6 n-3) [23][24][25] which is a natural compound present in our diet. It is incorporated at high levels in our cellular membranes and is devoid of side effects [26].…”
Section: Introductionmentioning
confidence: 99%